LOGISTIC ASPECTS OF WASTE MANAGEMENT IN CZĘSTOCHOWA REGION - Wolniakowska, Karina; Ławińska, Olga (Advanced Logistic Systems - Theory and Practice, 2016)
Last years occurred radical changes in waste management in Poland. The paper presents the legislation in force in this area and challenges facing communities. The changes introduced are designed to tighten the system, prevent waste, remove illegal landfill sites, increase the level of recovery from deposited waste and more. In order to achieve these objectives, it is necessary to introduce an integrated system for waste management using logistics. The paper presents selected elements of waste management logistics using Częstochowa region as an example.